Detailed simulation of dual-reflux pressure swing adsorption process. (27th January 2015) - Bhatt, Tushar S.; Storti, Giuseppe; Rota, Renato
Abstract: A model for the detailed simulation of dual-reflux pressure swing adsorption process developed in the frame of the commercial software Aspen Adsim ® is presented. For validation purposes, simulations were performed and model predictions were compared with published experimental results. At cyclic steady-state, model predictions were found to be in good agreement with reported experimental results in terms of (i) average ethane mole fraction in heavy product, (ii) average nitrogen mole fraction in light product, (iii) instantaneous heavy product composition profiles, and (iv) instantaneous column composition profiles. The predicted and experimental trends obtained by analyzing the effect of various operating parameters (light reflux flowrate, duration of feed/purge step, heavy product flowrate and mole fraction of heavy component in binary feed gas mixture) on process performance are also comparable. Overall, this simulation technique of dual-reflux pressure swing adsorption can serve as an effective tool for process design, cost reduction of laboratory and/or plant trails, and enhanced process understanding. Highlights: Aspen Adsim ® model for simulating realistic DR-PSA process scenarios is presented. The model is validated against 19 experimental DR-PSA runs. Model predictions are in good agreement with experimental results. Effect of feed position on process performance is also assessed via simulations.